Pengaruh Aktivitas Lembaga Keuangan Syariah terhadap Pertumbuhan Pembiayaan UMKM - Hariyanto Hariyanto; Bariyyatin Nafi'ah (ITB AAS INDONESIA Surakarta, 2022)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Return On Assets (ROA), Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR) on MSME Financing at Sharia Rural Banks in Indonesia for the 2015-2019 Period. This study uses multiple linear regression which is processed using Eviews 9. The results of this study indicate that ROA has no effect on MSME financing, but CAR, NPF AND FDR have a significant effect on MSME financing at Sharia Rural Banks.